Detox your department: A stage model for achieving cultural change - Christopher D Lantz; Steven Mark Elliott (Academic Chairpersons Conference Proceedings, 2016)
Throughout this interactive session, participants will learn the stages of group formation, identify a cultural destination for their units, and engage in moderated small group activities that will help them develop their own specific stage-appropriate action strategies designed to achieve the desired cultural transformation.
Keywords: Departmental culture; cultural change; stages of group formation